Evaluation of Antimicrobial Activity of the Aquatic Extract against Bacterial isolates from URTI in Babylon Province, Iraq - Ayad F. Alkaim (Journal of Global Pharma Technology, 2018)
Background, The other infections of patient in the hospitals may be occur resulting from high drug résistance bacteria and causes mortality. The study have been aimed to investigate the antibacterial activity of aqueous extract Borago officinalis L., Cydonia oblonga., Matricaria chamomilla against most prevalence pathogenic bacteria. Methods; the aqueous extract Borago officinalis L., Cydonia oblonga., Matricaria chamomilla were used to investigate the antibacterial activity pathogenic bacteria by Agar well diffusion method. Result; the Result showed that the crude of all plants extract have potential antibacterial activity. Conclusion; Based on the results it can be concluded that plants extract can inhibit bacterial colonization and adherence to upper respiratory tract infection, and provide production against different human pathogens and this may have clinical relevance.Keyword: Borago officinalis L, Cydonia oblonga, Matricaria chamomilla, Pathogenic bacteria.